PERAN SERTA KENDALA ORANGTUA DALAM PROSES PENDAMPINGAN BELAJAR DI RUMAH DI ERA PANDEMI COVID-19 - Inekke Fatimatus Hasna; Imas Srinana Wardani; Apri Irianto (Universitas Trilogi, 2021)
Parenthood is one of the important responsibilities for nurturing, guiding, and educating children in order to explore their potential and form a good person. The purpose. of this study is to. describe the role of parents in accompanying the success of children's learning during the pandemic and to describe the obstacles parents encountered while accompanying home learning. The research uses a qualitative research approach with data collection techniques Interview, Documentation, Questionnaire Results of analysis of parental interview data in the process of parenthood in home learning mentoring has